Effect of Magnetic Field on Diesel Engine Power Fuelled with Jatropha-Diesel Oil - Sukarni Sukarni; Partono Partono; Deni Krisdianto; Retno Wulandari (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
Jatropha oil has characteristics very close to the diesel fuel, so it has good prospects as a substitute or as a mixture of diesel fuel. Previous research showed that jatropha oil usage in diesel engines caused power to decrease. It was probably owing to the higher viscosity of the Jatropha oil compared to that of diesel oil. Installing the magnetic field in the fuel line of a diesel engine fueled with jatropha-diesel oil is expected to reduce the viscosity of jatropha-diesel oil mixture, hence improve the combustion reaction process. This research aims to know the influence of the magnetic field strength in the fuel lines to the power of diesel engines fueled with a mixture of jatropha-diesel oil. The composition of Jatropha oil-diesel was 20% jatropha oil and 80% diesel oil. Magnetic field variations were 0.122, 0.245 and 0.368 Tesla. The results showed that the higher the strength of the magnetic field was, the higher the average diesel engine’s power would be.